THE HISTORY OF THE FORMATION AND THE ROLE OF LEGAL CLINICS: A CASE STUDY OF THE YEREVAN STATE UNIVERSITY LEGAL CLINIC - Vardanyan, Qnarik (Bulletin of Yerevan University C: Jurisprudence, 2026)
The scientific article explores the historical evolution and development of legal clinics as student-led legal counseling centers. It examines the origins and global proliferation of the term "legal clinic," highlighting its integration into leading universities worldwide. The research emphasizes the dual significance of legal clinics- educational and social- focusing on their role in equipping law students with practical professional skills and in providing free, high-quality legal assistance to socially vulnerable populations. A significant part of the article focuses on the foundation and evolution of clinical legal education at the Faculty of Law of Yerevan State University, highlighting its origins, key developmental milestones, and the breadth of its current activities.